Worm control for small ruminants in the Philippines - Gray, G.D.; Yee, C.A.T.; Villar, E.C. (Australian Centre for International Agricultural Research, 2004)
The paper starts with a description of parasites of small ruminants in the Philippines. It then discusses host-parasite relationships and worm control options; looks into worm control programs; and examines impact of helminths on production. It then discusses anthelmintic plants and biological control; nutritional supplementation; genetic variation in production and resistance to disease; production differences between and within breeds; and use of anthelmintics and anthelmintic resistance. The paper also outlines measurement of production in grazing environments and looks into worm control programs in the Philippines. Nematode species included in the studies are Trichostrongylus sp., Haemonchus contortus, Oesophagostomum columbianum, Trichuris ovis, Eurytrema pancreaticum and Strongyloides papillosus.